Wildlife migrations highlight importance of both private lands and protected areas in the Greater Yellowstone Ecosystem. (November 2022) - Gigliotti, Laura C.; Xu, Wenjing; Zuckerman, Gabriel R.; Atwood, M. Paul; Cole, Eric K.; Courtemanch, Alyson; Dewey, Sarah; Gude, Justin A.; Hnilicka, Patrick; Hurley, Mark; Kauffman, Matthew; Kroetz, Kailin; et al.
Abstract: Formally protected areas are an important component of wildlife conservation, but face limitations in their effectiveness for migratory species. Improved stewardship of working lands around protected areas is one solution for conservation planning, but private working lands are vulnerable to development. In the Greater Yellowstone Ecosystem (GYE), ungulates such as elk ( Cervus canadensis ) use both protected areas and private lands throughout their annual migrations. We studied patterns of landownership, protection, and conservation challenges within the ranges of migratory elk in the GYE. We used GPS data from 1088 elk in 26 herds to define herd-level seasonal ranges, and extracted covariates related to landownership and protection, land use, and human infrastructure and development. All elk herds used land encompassing >1 ownership type. Most elk herds (92.3 % of herds, n  = 24) used the highest proportion of private land in the winter (mean = 36.2 % private land). Most elk herds' winter ranges contained the highest building densities (mean = 1.24 buildings/km 2 ), fence densities (mean = 1.02 km fence/km 2 ), and cattle grazing (mean = 1.9 cows/km 2 ), compared to migratory and summer ranges. Out of all ranges, 36.5 % of ranges did not have any zoning regulations, indicating the potential for future development. Our results show that elk in the GYE rely on habitat outside of protected areas, and face landscape-scale conservation challenges such as habitat fragmentation from human development, particularly in winter ranges. Future conservation strategies for wildlife in this system need to encompass coordination across both public and private land to ensure migratory connectivity.